Long-term surgical outcomes of primary retropupillary iris claw intraocular lens implantation for the treatment of intraocular lens dislocation - Choi, Eun Young (Sci Rep, 2021)
We aimed to investigate the efficacy and safety of primary retropupillary iris claw intraocular lens (R-IOL) implantation in patients with complete intraocular lens (IOL) dislocation. In this single-center retrospective case series, we reviewed the medical records of patients who underwent R-IOL implantation surgery with pars plana vitrectomy for the treatment of IOL dislocation between September 2014 and July 2019. The primary outcome was change in visual acuity (VA) up to 24 months postoperatively. The secondary outcomes included changes in intraocular pressure (IOP), refractive errors, and endothelial cell count (ECC) over the same period. Data of 103 eyes (98 patients) were analyzed. The mean uncorrected VA was significantly improved at one month postoperatively (− 0.69 logMAR, P < 0.001), compared to the preoperative value. IOP (− 2.3 mmHg, P = 0.008) and ECC (− 333.4 cells/mm(2), P = 0.027) significantly decreased one month post-surgery and remained stable thereafter. Postoperative mean spherical equivalents were similar to the prediction error throughout the follow-up period. IOP elevation (n = 8, 7.8%), cystoid macular edema (n = 4, 3.9%), and dislocation of the R-IOL (n = 10, 9.7%) were managed successfully. Overall, primary R-IOL implantation with pars plana vitrectomy is effective and safe for correcting IOL dislocation due to various causes.